Public Library System in Thiruvananthapuram, Kerala: An investigation - AjithaKumari, V. P.; Francis, A. T. (Journal of Information and Knowledge, 2015)
Public libraries provide a wide range of information products and services to the benefit of its user community. A public library is considered as gateway to knowledge, freedom, prosperity and the development of the society. The individuals in a society must have fundamental human values as per the UNESCO declaration. These are acquired by well informed citizens through playing an active part in social affairs and exercising their democratic rights. Constructive participation and the development of democracy depend upon satisfactory education as well as free and unlimited access to knowledge, thought, culture and information provided by public libraries. This study examines the role of public libraries in Kerala society. An attempt was made to evaluate the use of A-Grade public libraries in Thiruvananthapuram District by the users, purpose of using libraries, and present an overview of public libraries. This study suggests ways of reorienting the public libraries with IT enabled sources and services for the better development of the community as a whole.